Principles of Forensic Mental Health Assessment - Heilbrun, Kirk. (Perspectives in Law & Psychology,, 2001)
Most of the literature in forensic mental health assessment is organized around the particular legal issue that is the focus of a given assessment, tool, or research study. This book starts with a different assumption: There are broad principles of forensic assessment that are applicable across different legal issues. If such principles exist, they should be derived from and supported by sources of authority in ethics, law, science, and prof- sional practice. This is what I seek to do in this book, with each of the 29 broad principles of forensic mental health assessment described and a- lyzed from the perspective of these sources of authority. There are a number of individuals who have contributed in various ways to making this a better book. It seems best to begin with a general acknowledgment: Those interested in forensic mental health assessment, particularly my colleagues from the American PsychologyỚ<U+001c>Law Society and the American Board of Forensic Psychology, have been an extraor- narily helpful and congenial group. I have learned a great deal from them over the years and they challenged me to undertake the daunting task of trying to capture the broad views of the field in this book.